Epidermal growth factor-stimulated phosphoinositide hydrolysis in cultured rat inner medullary collecting tubule cells. Regulation by G protein, calcium, and protein kinase C. - Teitelbaum, I (1990)
Epidermal growth factor (EGF) exhibits specific saturable binding to cultured rat inner medullary collecting tubule cells and stimulates inositol trisphosphate (IP3) production by these cells in a dose-dependent fashion. EGF-stimulated IP3 production is enhanced by GTP gamma s or AIF4- and is inhibited by GDP beta s or pertussis toxin. Alterations in extracellular Ca2+ have no effect on either basal or EGF-stimulated IP3 production. Similarly, treatment with EGTA which decreases cytosolic Ca2+ is without effect. In contrast, treatment with ionomycin which increases cytosolic Ca2+ has no effect on basal IP3 production but enhances the response to EGF. Activation of protein kinase C inhibits IP3 production in response to either EGF or AIF4-. These studies demonstrate the occurrence of EGF-stimulated phospholipase C activity in the rat inner medullary collecting duct. Stimulation by EGF is transduced by a pertussis toxin-sensitive G protein, unaffected by alterations in extracellular Ca2+, insensitive to a decrement in cytosolic Ca2+, enhanced by an increase in cytosolic Ca2+, and inhibited by protein kinase C.